Stakeholders’ perceptions of integrated rainwater management approaches in the Blue Nile Basin of the Ethiopian highlands - Mulema, Annet A.; Lema, Zelalem; Damtew, Elias; Adie, Aberra; Ogutu, Z.; Duncan, Alan J. (Wiley, 2017)
Previous approaches to improve soil and water management in the Ethiopian highlands have achieved marginal success. An integrated approach to rainwater management (RWM) has been piloted to address interrelated problems of land degradation, livestock feed shortage, and soil erosion, in an effort to improve the resilience of rural livelihoods. However, stakeholders’ perceptions about the approach have not been documented. Using data from in-depth interviews, this study assesses stakeholders’ knowledge, attitudes, skills and practices in the Diga, Jeldu and Fogera districts of Ethiopia. Our study finds gender differences in knowledge and application of integrated RWM strategies amongst farmers. Stakeholders interviewed appreciate fodder development because it directly addresses land degradation and livestock feed shortage, and provides extra benefits to the households. There are differences in successful RWM practices across the districts. Planners, researchers and policy makers engaged in innovation platforms have an increased understanding of the tools to engage multiple stakeholders in planning for RWM. However, inflexible extension approaches and other contextual issues limit wide-scale use of bottom-up approaches. We conclude that approaches to RWM that are holistic and engage diverse stakeholders foster the uptake of innovations. Awareness creation, collaboration, capacity development, incentives, monitoring, political will and favorable gender norms are vital to the process.